Clinical improvement may not reflect metabolic homeostasis normalization in subjects with and without Roux-En-Y bariatric surgery after 12 years: comparison of surgical subjects to a lean cohort - Butler, Alexandra E.; Ramanjaneya, Manjunath; Moin, Abu Saleh Md; Hunt, Steven C.; Atkin, Stephen L. (Frontiers in Endocrinology, 2023)
Background. A 12-year study comparing clinical outcomes following Roux-en-Y bariatric surgery showed long-term weight loss with remission/prevention of type-2-diabetes (T2D), hypertension and dyslipidemia. However, it is unknown whether the underlying homeostatic metabolic processes involving hepatokines, adipokines and myokines also normalize. Using this 12-year study, we determined whether metabolic indices improved in post-surgical (BMI:34.4kg/m2) versus non-surgical comparator-subjects-with-obesity (BMI:43.8kg/m2) at 12-year follow-up (both cohorts with baseline diabetes), and if post-surgical subjects normalized their metabolic processes to those of a normal-weight cohort without diabetes. Methods. Cross-sectional design. Plasma from a cohort of Roux-en-Y bariatric surgery (n=50) and non-surgery (n=76) comparator-subjects-with-obesity (both cohorts at 12-year follow-up) plus a normal-weight cohort (n=39) was assayed by Luminex immunoassay or ELISA for hepatokines [angiopoietin-like proteins-(ANGPTL3; ANGPTL4; ANGPTL6); fibroblast growth factors-(FGF19; FGF21; FGF23)]; adipokines [adipsin; adiponectin; FGF19] and myonectin. Results. After age and gender adjustment, surgery versus comparator-subjects-with-obesity had lower BMI (34.4±1.0 vs 43.8±0.9kg/m2; p<0.0001), HbA1c (6.2±0.3 vs 7.7±0.2%; p<0.0001), insulin resistance (HOMA-IR, 2.0±1.5 vs 10.8±1.4; p<0.0001) fat mass (45.6±2.2 vs 60.0±2.0; p<0.0001), HDL-C (55.4±2.6 vs 42.6±2.3mg/dL; p<0.0001), triglycerides (130±14 vs 187±12mg/dL; p<0.0001) and higher adiponectin (25.9±2.3 vs 15.7±2.0µg/ml; p<0.001); Adipsin, ANGPTL3, ANGPTL4, ANGPTL6, FGF19, FGF21, FGF23 and myonectin did not differ. Surgery versus normal-weight group: higher ANGPTL4 (156±6 vs 119±7ng/mL; p<0.0001), higher FGF23 (96.4±10.1 vs 50.9±11.5pg/mL; p=0.007) and lower myonectin (744±55 vs 969±66ng/mL; p=0.002); adiponectin, adipsin ANGPTL3, ANGPTL6, FGF19, FGF21 did not differ. Non-surgery comparator-subjects-with-obesity versus normal-weight group: higher adipsin (1859±94 vs 1314±133ng/mL; p=0.0001), higher FGF23 (84.6±8.5 vs 50.9±11.5pg/mL; p<0.0001) and higher ANGPTL4 (171±5 vs 119±7ng/mL; p<0.0001); adiponectin ANGPTL3, ANGPTL6, FGF19, FGF21 and myonectin did not differ. Conclusions. Bariatric surgery markedly improved anthropometric and metabolic features versus comparator-subjects-with-obesity at 12-year follow-up, indicating benefit of weight loss. However, despite weight loss, these patients still had class-1 obesity, as reflected in the adipokine, hepatokine and myokine markers of body homeostasis that did not completely normalize to indicative values of normal-weight subjects, suggesting either that this is the new normal for these patients or that weight loss to a BMI<25kg/m2 is needed for normalization of these parameters.